Information and Communications Technology-Based Monitoring Service for Tailored Chronic Disease Management in Primary Care: Cost-Effectiveness Analysis Based on ICT-CM Trial Results - Sung-Hee Oh; Jae-Heon Kang; Jin-Won Kwon (JMIR Publications, 2024)
BackgroundInformation and communications technology-based tailored management (TM) intervention is a novel automatic system in which a smartphone app for the management of patients with hypertension and diabetes, the provider web, and Bluetooth devices are linked. However, little evidence exists regarding the cost-effectiveness of the interventions using mobile apps. ObjectiveThis study aimed to assess the cost-effectiveness of TM intervention for adult patients with hypertension or diabetes in primary care compared with usual care (UC). MethodsCost-effectiveness analysis using a Markov model was conducted from the Korean health care system perspective. Based on 6-month outcome data from an information and communications technology-based tailored chronic disease management (ICT-CM) trial, effectiveness over a lifetime beyond the trial periods was extrapolated using a cardiovascular disease risk prediction model. Costs were estimated using ICT-CM trial data and national health insurance claims data. Health utility weights were obtained from the Korea National Health and Nutrition Examination Survey. ResultsIn the base-case analysis, compared with UC, TM was more costly (US $23,157 for TM vs US $22,391 for UC) and more effective (12.006 quality-adjusted life-years [QALYs] for TM vs 11.868 QALYs for UC). The incremental cost-effectiveness ratio was US $5556 per QALY gained. Probabilistic sensitivity analysis showed that the probability of TM being cost-effective compared with UC was approximately 97% at an incremental cost-effectiveness ratio threshold of US $26,515 (KRW 35 million) per QALY gained. ConclusionsCompared with UC, TM intervention is a cost-effective option for patients with hypertension or diabetes in primary care settings. The study results can assist policy makers in making evidence-based decisions when implementing accessible chronic disease management services.